Community Treatment Orders: Implications of the drafting of the Mental Health Act 2007 for emergency detention of Community Patients. (January 2015) - Wood, Julie; Wood, Robin; Falkowski, Jan; Butler, Josh
Since the introduction of Community Treatment Orders by the Mental Health Act 2007, their use has increased year on year. Clinical experience has, however, demonstrated a weakness in the drafting of the Act, particularly in respect of patients who may be admitted informally for treatment of their mental health while also on a Community Treatment Order and then require detention under the terms of the Mental Health Act 2007. This paper describes these potential problems, particularly with regard to the inability to detain a Community Patient using sections 4 or 5 of the MHA 2007. The authors explore the difficulties that may arise from this, including the need to balance the principle of using the least restrictive option, and the rights of the patient against the potential risks to both the patient and the public. The authors propose possible considerations and options in these circumstances.